Systematic review of the outcome of single-anastomosis sleeve ileal (SASI) bypass in treatment of morbid obesity with proportion meta-analysis of improvement in diabetes mellitus. (August 2021) - Emile, Sameh Hany; Mahdy, Tarek; Schou, Carl; Kramer, Michael; Shikora, Scott
Abstract: Background: Single-anastomosis sleeve ileal (SASI) bypass has emerged as a promising bariatric and metabolic procedure. We aimed to review the current literature on the outcome of SASI procedure in terms of weight loss, improvement in comorbidities, and complications. Methods: We conducted a systematic literature search, querying electronic databases and Google Scholar, for studies that reported the outcome of the SASI bypass. The main outcome measures of the review were change in body mass index (BMI), % of excess weight loss (%EWL), improvement in comorbidities, and complications after SASI bypass. Results: This systematic review comprised ten studies including 941 patients with a median BMI of 45.6 kg/m 2 . The median %EWL at 6 months was 59.4% and significantly (p = 0.04) increased to 90.1% at 12 months. The weighted mean rate of improvement in diabetes mellitus was 99.1 (95%CI: 98.2–99.9, I 2  = 0). The crude percentages of patients with improvement in hypertension, hyperlipidemia, and gastroesophageal reflux disease were 51%, 76.6%, and 92%, respectively. The median operation time was 111.3, ranging between 75 and 148.4 min. Complications were recorded in 116 (12.3%) patients. Longer common limb was associated with less %EWL at 6 months and less complications whereas larger anastomosis size was associated with higher weight loss and greater improvement in hypertension. Conclusions: SASI bypass was associated with good short-term outcomes in regard to weight loss and improvement in comorbidities, namely diabetes mellitus with an acceptably low complication rate. Highlights: Ten studies (941 patients) were included. The median excess weight loss at 12 months was 90.1%. The weighted mean rate of improvement in diabetes mellitus was 99.1. Improvement rates of hypertension, hyperlipidemia, and GERD were 51%, 76.6%, and 92%. The median operation time was 111.3 min and complications rate was 12.3%.